Sobre a justiça no comércio e as escolhas morais de consumo : o caso dos consumidores de Comércio Justo - Sandra Lima Coelho (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2015)

(untitled)
In this paper we present some results of a research project about Fair Trade (FT) consumers in Portugal. One analyses consumers’ practices and the reasons that lead to purchase products from this new social and economic movement. The analysis of the data reveals that the reasons that lead consumers to FT are plural: the consumption of FT products can express individual preferences that concern not only to the taste, quality or exoticism of these goods, but also to the consumers’ moral values.